Transformation of Prayer Time Schedules: from A Static-Passive to A Dynamic-Variative Perspective - Riza, Muhammad Himmatur; Djamaluddin, Thomas; Izzuddin, Ahmad (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2022)
Prayer times are extremely important for Muslims, as they serve as a guide for the beginning of prayer times. However, there are still people who do not fully understand the impact of changes in the position of the Sun, which causes the start of prayer times to change daily. Additionally, some people still use perpetual prayer time schedules. Although they use the term "perpetual," in reality, prayer time schedules are not everlasting, as they cannot be used over long periods. This research is a library study with a phenomenological-astronomical approach. The results of this study show that prayer times change every day. Someone who believes that the start of Maghrib prayer is always at 18:00 WIB and the start of Fajr prayer is always at 04:30 WIB may find that on some days, their prayer or fasting is invalid, as the start of Maghrib prayer may occur between 18:01 and 18:08 WIB and the start of Fajr prayer may occur between 04:31 and 04:34 WIB. These changes can serve as an understanding for the community that the correctness of prayer time schedules is not static-passive but dynamic-variable. This means that the start of prayer times each day and year is not always the same as the following days and years, and the changes vary. Therefore, this study provides a scientific guide for the community to better understand and be cautious in using prayer time schedules, considering that the beginning of prayer times determines the validity of a Muslim's prayer.